Faktor Yang Berhubungan Dengan Stres Kerja Pada Perawat di Ruang Rawat Inap RSUD Lasinrang (Window of Public Health Journal, 2025)
Stress is a non-specific response of the body to any demands or burdens given. Stress can arise when a person experiences a heavy burden or task and cannot cope with the assigned task. This study aims to determine the factors related to work stress in nurses in the inpatient ward installation at the Lasinrang Regional General Hospital, Pinrang Regency, in 2024. This study uses a quantitative research method with a cross-sectional research design. Sampling in this study was simple random sampling with a sample size of 104 nurses. The analysis used was univariate and bivariate analysis with the chi-square test. The results of the study showed that age (p 0.001